2001
DOI: 10.1016/s0014-5793(01)02103-2
|View full text |Cite
|
Sign up to set email alerts
|

Early signaling components in ultraviolet‐B responses: distinct roles for different reactive oxygen species and nitric oxide

Abstract: The nature and origin of the reactive oxygen species (ROS) involved in the early part of Ultraviolet-B (UV-B)-induced signaling pathways were investigated in Arabidopsis thaliana using a range of enzyme inhibitors and free radical scavengers. The increase in PR-1 transcript and decrease in Lhcb transcript in response to UV-B exposure was shown to be mediated through pathways involving hydrogen peroxide (H(2)O(2)) derived from superoxide (O(2)(&z.rad;-)). In contrast, the up-regulation of PDF1.2 transcript was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
217
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 389 publications
(234 citation statements)
references
References 32 publications
8
217
0
5
Order By: Relevance
“…Interestingly, it has been shown that: (1) the induction of CHS expression may be co-ordinately regulated by UV-B and nitric oxide (NO) (Mackerness et al 2001); and (2) NO regulates the binding of the AtMYB2 TF to DNA in vitro (Serpa et al 2007). NO is a ubiquitous bioactive molecule, produced in plants by enzymatic and nonenzymatic routes (see Wilson, Neill & (Beligni & Lamattina 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has been shown that: (1) the induction of CHS expression may be co-ordinately regulated by UV-B and nitric oxide (NO) (Mackerness et al 2001); and (2) NO regulates the binding of the AtMYB2 TF to DNA in vitro (Serpa et al 2007). NO is a ubiquitous bioactive molecule, produced in plants by enzymatic and nonenzymatic routes (see Wilson, Neill & (Beligni & Lamattina 2000).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the enzymatic source of H 2 O 2 mediating UV-B-induced stomatal closure, our previous study has provided pharmacological evidence that 0.8 W m 22 UV-B-induced H 2 O 2 generation in broad bean guard cells depends on peroxidases but not NADPH oxidases (He et al, 2011a). However, UV-B is reported to stimulate mRNA transcript levels and the activity of NADPH oxidases (Rao et al, 1996;A-H-Mackerness et al, 2001;Casati and Walbot, 2003), and mutants in the Arabidopsis AtrbohD and AtrbohF genes show reduced H 2 O 2 accumulation in response to UV-B (Kalbina and Strid, 2006), suggesting that NADPH oxidases are also potential sources of H 2 O 2 induced by UV-B. To explore whether different doses of UV-B can activate distinct sources of H 2 O 2 to induce stomatal closure, we examined H 2 O 2 sources during stomatal closure induced by 0.5 and 0.7 W m 22 UV-B.…”
Section: Ga Plays An Important Role In Uv-b Guard Cell Signalingmentioning
confidence: 99%
“…This plant has been used in many plant studies to determine the involvement of NO in seed germination (Beligni and Lamattina, 2000;Batak et al, 2002;Bethke et al, 2006), biotic stress (Delledonne et al, 1998(Delledonne et al, , 2001), abiotic stress (Mackerness et al, 2001;Huang et al, 2004), programmed cell death (Clarke et al, 2000;Zhang et al, 2003), stomatal closure (Garcia-Mata et al, 2003;Desikan et al, 2004), iron metabolism (Murgia et al, 2004;Perazzolli et al, 2004), flowering (He et al, 2004;Simpson, 2005), and the protein S-nitrosylation (Feechan et al, 2005;Lindermayr et al, 2005), among others. Using the DAF-FM DA as a fluorescence probe, our results provide a detailed picture of the overall distribution of NO during the early development of 3-to 11-d-old Arabidopsis seedlings.…”
Section: No Is Present In Cotyledons and Roots During The Developmentmentioning
confidence: 99%